PERKEMBANGAN NAHDLATUL ULAMA (NU) DI KOTA PONTIANAK DARI TAHUN 1998-2018 - Patmawati, Patmawati; Sastrawan Noor, Agus; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the development of the NahdlatulUlama (NU) in Pontianak City in 1998-2018. The formulation of the problem  in this study discribes a brief history of the NadlatulUlama (NU) in Indonesia, the background of the establishment of the NahdlatulUlama (NU) in Pontianak and its development from 1998 until 2018. Historical research method was applied in conducting this research. The steps used in this method consist of topic selection, heuristics, verification, interpretation, and historiography. The findings showed that the establishment of the NU began with the arrival of transmigrants from Java and Madura that include clerics and their students from Islamic boarding schools in Madura. The background of this establishment is to spread Islam AhlussunnahWalJama’ah. Furthermore, the people in Pontianak needed an equal umbrella of organization as before NU entered Pontianak City, its practices had alredy existed in Pontianak City.  Keywords: Development, Nahdlatul Ulama (NU), Pontianak City